Towards improving the quality of internships in medicine and allied health professions - Jankowicz-Szymańska, Agnieszka; Kołpa, Małgorzata; Stefanowicz-Kocoł, Anna; Konstantinidis, Statis Th.; Ko, Stan; Henderson, James; Cunningham, Sheila; Hodge, Pam; Tilley, Zoë; Höijer-Brear, Viveka; Törne, Marika; Lillo-Crespo, Manuel; et al. (Health Promotion & Physical Activity, 2023)
Introduction: One of the important elements influencing the well-being of society is a highly educated, professional staff of the entire therapeutic team. Physiotherapists play a significant role in this team, which is why the higher education system is expected to make efforts to develop optimal education programs, including the development of practical skills. The purpose of this article is to present the Healint4All project, whose mission is to facilitate international internships for students of physiotherapy and other medical professions, which will allow high-class professionals in the healthcare sector to enter the job market. Material and methods: A step-by-step process of creating a protocol for auditing places of clinical practice was prepared. Virtual, interactive teaching resources were developed to prepare auditors. A literature analysis, focus interviews in groups of academic teachers, practitioners, and students. A pilot study of the protocol in live environments was conducted. Results: Both potential auditees (medical institutions) and auditors (universities) positively assessed the newly created tool. The recommendations included paying attention to transparency, simplicity, and linguistic correctness in all language versions of the protocol. It was suggested that the protocol, containing everything useful, should not be too long and would not burden the user with time. Conclusions: In the opinion of students and experts who evaluated the Healint4All protocol, it will contribute to increasing the supply and quality of international placements offered by healthcare organizations throughout Europe, as well as simplifying the processes involved in organizing these for students, educational institutions, and healthcare organizations.